What do parents think about their involvement in speech-language pathology intervention? A qualitative critically appraised topic. Issue 1 (3rd April 2019) - Skeat, Jemma; Roddam, Hazel
Abstract: A critically appraised topic (CAT) is one form of rapid review that can be particularly useful for informing practice. The purpose of this CAT was to determine what caregivers of preschool-aged children with speech, language or communication disorders (2–5 years of age) think of their involvement in speech-language pathology intervention in community-based settings. In addition to this CAT, the authors present and discuss a methodology for qualitative critically appraised topics (this issue). The authors propose an update to this CAT in June 2021.